Metodologi Al-Asy’ari (Studi atas Bangunan Teologi Al-Asy’ari) - Muhyidin Muhyidin; Zamroni Ishaq (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
The A thought cannot be separated from the historical context in which the thinker lived. Al-Ash'ari lived in an atmosphere of conflicting ideas, between the highly rational Mu'tazilites on the one hand, and the highly textual Hanabilah (Hadith or Salafists), on the other. At first, al-Ash'ari was a loyal follower of the Mu'tazilites, then at the age of 40 he left the Mu'tazilites. There were many reasons behind al-Ash'ari coming out of the Mu'tazilites. But most importantly, after al-Ash'ari left the Mu'tazilites, he developed a concept of thought that sought to combine the rational method of the Mu'tazilites and the textual method of Hanabilah. Not only that, in order to prove the truth of his thoughts, al-Asha'ri attacked the Mu'tazilite thoughts. Therefore, it can be concluded that the method used by al-Ash'ari in constructing his theology was to use the 'middle axis' methodology; synthesis between textual and rational. It was this methodological building pattern that ultimately led to Asharite theology being followed by the majority of Muslims in the world today.